2022
DOI: 10.1038/s41598-022-14071-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 conspiracy ideation is associated with the delusion proneness trait and resistance to update of beliefs

Abstract: The rapid spread of conspiracy ideas associated with the recent COVID-19 pandemic represents a major threat to the ongoing and coming vaccination programs. Yet, the cognitive factors underlying the pandemic-related conspiracy beliefs are not well described. We hypothesized that such cognitive style is driven by delusion proneness, a trait phenotype associated with formation of delusion-like beliefs that exists on a continuum in the normal population. To probe this hypothesis, we developed a COVID-19 conspiracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…First, this is a relatively small dataset, and even smaller for those with Horizon task data, which can increase the risk of false positives and false negatives 55 , such as our failure to replicate previous differences between HCs and schizophrenia patients in directed exploration. However, similar effect sizes to those observed in much larger studies 29 , 31 , 32 , 53 increase our confidence in the significant results we observed. Additionally, the third-level volatility parameters within the reversal learning dataset ( , and ) did not demonstrate robust recoverability in simulation (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, this is a relatively small dataset, and even smaller for those with Horizon task data, which can increase the risk of false positives and false negatives 55 , such as our failure to replicate previous differences between HCs and schizophrenia patients in directed exploration. However, similar effect sizes to those observed in much larger studies 29 , 31 , 32 , 53 increase our confidence in the significant results we observed. Additionally, the third-level volatility parameters within the reversal learning dataset ( , and ) did not demonstrate robust recoverability in simulation (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the exploratory finding of a relationship between learning rate for volatility (meta-volatility) from the reversal learning task ( ) and both initial learning rate on the Horizon task and BADE evidence integration impairment (EII) is intriguing. The BADE-EII variable is relatively new variable for analyzing BADE data and was recently shown to be associated with delusional ideation and conspiracy beliefs in the general population 53 . The calculation of BADE-EII is based on the average plausibility rating for implausible items, but it does not take into account change in rated plausibility of that item after new evidence is presented.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on whether these processes relate to why delusion-related phenotypes more readily acquire delusion-like ideas including conspiracy narratives outside the experimental setting. 93 , 94 …”
Section: Evidence For Overly Precise High-level Priorsmentioning
confidence: 99%
“…There are “lure” interpretations that seem highly plausible initially but are rendered increasingly unlikely as more information is revealed. Patients with schizophrenia, 97–101 schizotypical individuals, 102 , 103 and healthy individuals with high delusion-proneness 93 , 94 , 104 , 105 typically stick longer to their first choices, that is, they more often fail to adequately down-rate the plausibility of lure interpretations. This failure to integrate new information that contradicts an initially formed belief is again in line with the Bayesian notion of overly precise high-level beliefs.…”
Section: Evidence For Overly Precise High-level Priorsmentioning
confidence: 99%
“…Importantly, these peculiarities in the predictive style that characterize positive SSD and ASD could subserve a different disposition toward vaccines. Since higher levels of positive schizotypy and delusion proneness have been associated to anti-scientific beliefs (i.e., telepathy; Raine, 1991), to conspiracy theory about COVID-19 (Larsen et al, 2021;Acar et al, 2022), to prior-driven perception (Schmack et al, 2013) and individuals with psychotic disorders tend to refuse COVID-19 vaccination more than the general population (Hassan et al, 2022), we hypothesize that individuals lying toward the positive SSD pole of the continuum may show a general negative attitude toward vaccines. Furthermore, it is possible to speculate that the propensity for deliberate processing and the tendency to gather much evidence before making a decision observed in ASD may be related to a positive attitude toward vaccination, as the adoption of a deliberative and analytical thinking style increases the inclination to reject COVID-19 conspiracy theories/theorists (Swami and Barron, 2021).…”
Section: Introductionmentioning
confidence: 97%